2012
DOI: 10.4161/cbt.19241
|View full text |Cite
|
Sign up to set email alerts
|

Spermine synthase overexpression in vivo does not increase susceptibility to DMBA/TPA skin carcinogenesis or Min-Apc intestinal tumorigenesis

Abstract: Numerous studies have demonstrated a link between elevated polyamine biosynthesis and neoplastic growth, but the specific contribution of spermine synthase to epithelial tumor development has never been explored in vivo. Mice with widespread overexpression of spermine synthase (CAG-SpmS) exhibit decreased spermidine levels, increased spermine and a significant rise in tissue spermine:spermidine ratio. We characterized the response of CAG-SpmS mice to two-stage skin chemical carcinogenesis as well as spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Very recent immunoprecipitation and immunohistochemistry studies in human chondrocytes and in vivo study conducted in mice reported that the cells treated with spermidine (100 nmol/L) showed autophagy activation and promoted chondrogenesis [98] . However, spermidne role in cancer is still controversial as some studies reported that spermidine do not induce tumorigenesis [99] , whereas some studies established that spermidine synthase inhibitors show little cell growth reduction in cancer cell lines [100] .…”
Section: Spermidinementioning
confidence: 99%
“…Very recent immunoprecipitation and immunohistochemistry studies in human chondrocytes and in vivo study conducted in mice reported that the cells treated with spermidine (100 nmol/L) showed autophagy activation and promoted chondrogenesis [98] . However, spermidne role in cancer is still controversial as some studies reported that spermidine do not induce tumorigenesis [99] , whereas some studies established that spermidine synthase inhibitors show little cell growth reduction in cancer cell lines [100] .…”
Section: Spermidinementioning
confidence: 99%
“…Indeed, increased epidermal AdoMetDC expression suppresses skin tumor promotion in DMBA-initiated/TPA-promoted mice (Shi et al 2012). Moreover, increased epidermal spermine synthase activity has no effect on skin tumor development in transgenic mice subjected to a DMBA/TPA carcinogenesis protocol (Welsh et al 2012). Surprisingly, K6/SSAT transgenic mice with increased epidermal expression of SSAT are more sensitive to skin tumor development when subjected to a DMBA initiation/TPA promotion protocol (Coleman et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of MYC is a consequence of mutations in APC, a central hub in early colorectal carcinogenesis 58 . In a mouse model of Min-Apc intestinal tumorigenesis, mice that overexpressed SMS display similar colon tumor multiplicity and size compared with multiple intestinal neoplasia as seen in the Min mice 59 . Together, these data suggest that SMS alone does not promote CRC tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%